PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI GURU KELAS DI SD NEGERI 3 REJOSARI KABUPATEN OKU TIMUR - Rahmat, Nur; Sepriadi, Sepriadi; Daliana, Rasmi (Graduate Program Magister Manajemen Pendidikan, 2017)
The role of educators should be able to carry out the inspiration of learning. The existence of teachers as one component in the education system greatly affects the formation of student discipline character in SD Negeri 3 Rejosari Belitang Mulya District, OKU Timur. This research was descriptive qualitative. This research provided an overview of the character of students’ discipline and provide solutions in character-based learning for students in OKU Timur. Data collection techniques used in this study were observation, interviews, and documentation. The results of this study explained that teachers as educators, teachers as teachers, teachers as mentors, teachers as trainers, and teachers as evaluators. The role of classroom teachers in SD Negeri 3 Rejosari has been good already, because each class teacher has applied the five aspects of the role of the class teacher well. Efforts of classroom teachers in the formation of student character are using habituation method, exemplary, lecture and simulation. Therefore, teachers have an important role in building the character of the nation.